Microarray-based identification of differentially expressed genes in families of turbot (Scophthalmus maximus) after infection with viral haemorragic septicaemia virus (VHSV) - Díaz-Rosales, Patricia; Romero Jódar, Alejandro; Balseiro, P.; Dios, S.; Novoa, Beatriz; Figueras Huerta, Antonio (Marine Biotechnology, 2012)
15 páginas, 4 figuras, 4 tablas.-- The original publication is available at www.springerlink.com Viral haemorrhagic septicaemia virus (VHSV) is one of the major threats to the development of the aquaculture industry worldwide. The present study was aimed to identify genes differentially expressed in several turbot (Scophthalmus maximus) families showing different mortality rates after VHSV. The expression analysis was conducted through genome-wide expression profiling with an oligo-microarray in the head kidney. A significant proportion of the variation in the gene expression profiles seemed to be explained by the genetic background, indicating that the mechanisms by which particular species and/or populations can resist a pathogen(s) are complex and multifactorial. Before the experimental infections, fish from resistant families (low mortality rates after VHSV infection) showed high expression of different antimicrobial peptides, suggesting that their pre-immune state may be stronger than fish of susceptible families (high mortality rates after VHSV infection). After infection, fish from both high- and low-mortality families showed an up-modulation of the interferon-induced Mx2 gene, the IL-8 gene and the VHSV-induced protein 5 gene compared with control groups. Low levels of several molecules secreted in the mucus were observed in high-mortality families, but different genes involved in viral entrance into target cells were down-regulated in low-mortality families. Moreover, these families also showed a strong down-modulation of marker genes related to VHSV target organs, including biochemical markers of renal dysfunction and myocardial injury. In general, the expression of different genes involved in the metabolism of sugars, lipids and proteins were decreased in both low- and high-mortality families after infection. The present study serves as an initial screen for genes of interest and provides an extensive overview of the genetic basis underlying the differences between families that are resistant or ...